Optimizing a new 5-day CIDR-CO-Synch timed artificial insemination program - Stevenson, Jeffrey S.; Pulley, Stephanie Leeann; Mellieon, H.I.; Olson, K. C.; Johnson, Sandra K.; Grieger, David M.; Jaeger, John R.; Breiner, Ryan M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
The 7-day CO-Synch + CIDR protocol is a popular ovulation-synchronization program used by cow-calf producers to facilitate artificial insemination (AI). A progesterone- impregnated controlled internal drug release (CIDR) insert is placed intravaginally and an injection of gonadotropin-releasing hormone (GnRH) is given. After 7 days, prostaglandin F2α (PGF2α) is administered and the CIDR insert is removed. Between 58 and 72 hours after insert removal, cows are inseminated after another injection of GnRH to induce ovulation. Timed AI pregnancy rates generally have ranged from 40 to 60% when suckled cows are treated with the 7-day CO-Synch + CIDR protocol.
Beef Cattle Research, 2011 is known as Cattlemen’s Day, 2011
Keywords: Beef; CIDR-CO-Synch; Time artificial insemination